2018
DOI: 10.1177/2378023118769550
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Social Attitudes

Abstract: Gender, race, and class strongly predict social attitudes and are at the core of social scientific theory and empirical analysis. Sexuality (i.e., sexual orientation), however, is not as central a factor by which we conceptualize and systematize society. This study examines the impact of sexual orientation, gender, race, and education across attitudinal topics covered by the General Social Survey. Sexual orientation is an important part of people’s lives that, as I demonstrate, is a strong and exceptionally co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 98 publications
4
65
0
3
Order By: Relevance
“…In many contexts, women are more likely to claim liberal identities, espouse egalitarian values, and vote for progressive politicians (Beutel and Marini 1995;Box-Steffensmeier, DeBoef, and Lin 2004;Charrad 2011;Davis and Robinson 1991;Hadler 2012;Inglehart and Norris 1999;Manza and Brooks 1998;McDermott 2016;Pratto, Stallworth, and Sidanius 1997;Shapiro and Mahajan 1986). Yet, in a gender-and-politics paradox, women are just as if not more conservative than men on certain issues related to notions of "traditional morality"-including gender-related issues such as abortion-in at least some contexts (Barkan 2014;Schnabel 2018). In another gender paradox, religion tends to be mendominated and yet women-populated .…”
Section: Gender Differences In Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In many contexts, women are more likely to claim liberal identities, espouse egalitarian values, and vote for progressive politicians (Beutel and Marini 1995;Box-Steffensmeier, DeBoef, and Lin 2004;Charrad 2011;Davis and Robinson 1991;Hadler 2012;Inglehart and Norris 1999;Manza and Brooks 1998;McDermott 2016;Pratto, Stallworth, and Sidanius 1997;Shapiro and Mahajan 1986). Yet, in a gender-and-politics paradox, women are just as if not more conservative than men on certain issues related to notions of "traditional morality"-including gender-related issues such as abortion-in at least some contexts (Barkan 2014;Schnabel 2018). In another gender paradox, religion tends to be mendominated and yet women-populated .…”
Section: Gender Differences In Valuesmentioning
confidence: 99%
“…And, in what I call an underdog paradox, there are even issues where we might expect women to be more liberal but they can actually be significantly more conservative (e.g., abortion) (Barkan 2014). In fact, a recent study found that women tend to be no more liberal or even significantly more conservative than men on many specific social issues, especially those issues-like sexuality, abortion, and suicide-linked to religious norms and prohibitions (Schnabel 2018). Why are women and other disadvantaged groups not as liberal as we might expect on the basis of status-based theories of political values?…”
mentioning
confidence: 95%
“…The status, positionality, and politics literature shows that women and racial minorities are more progressive on issues related not just to their own wellbeing, but across other issues as well (e.g., women tend to hold less racist attitudes than men). A recent study applied the positionality principle to sexual minorities-who tend to be less religious and practice more inclusive forms of religion due to their marginalization by many religious groups-and found they're consistently more liberal than heterosexuals (Schnabel 2018b). In that study, women and Black Americans were more liberal on many topics, but on social issues tied to traditional religious teachings-such as abortion, sexuality, and suicide-they were just as if not more conservative than their more advantaged counterparts.…”
Section: Religion and Apparent Inconsistencies In The Positionality Pmentioning
confidence: 99%
“…And in American religion, belief systems (e.g., biblical literalism) and groups (e.g., fundamentalists) that emphasize an interventionist God demonstrate especially large status differences in adherence and particularly conservative system-justifying schemas (Hoffmann and Bartkowski 2008). Supporting the possibility that American religion is, on average, an actively socio-politically conservatizing force, it is primarily issues linked to religion on which disadvantaged groups are sometimes more conservative than their counterparts (Adamczyk et al 2016;Barkan 2014;Schnabel 2018b).…”
Section: Religion and Apparent Inconsistencies In The Positionality Pmentioning
confidence: 99%
See 1 more Smart Citation